Neoadjuvant chemotherapy combined with antiangiogenic therapy and immune checkpoint inhibitors for the treatment of locally advanced gastric cancer: a real - world retrospective cohort study - Zhan, Zhouwei; Chen, Bijuan; Xu, Shaohua; Lin, Ruyu; Chen, Haiting; Ma, Xiaohuan; Lin, Xuanping; Huang, Wanting; Zhuo, Changhua; Chen, Yu; Guo, Zengqing (Frontiers in Immunology, 2025)
BackgroundAlthough immune checkpoint inhibitors (ICIs) and anti-angiogenic drugs have demonstrated effectiveness in treating advanced gastric cancer (GC), their role in neoadjuvant or conversion therapy remains uncertain. This study aimed to evaluate the efficacy and safety of combining neoadjuvant chemotherapy with anti-angiogenesis and ICIs in patients with locally advanced GC (LAGC).MethodsIn this cohort study, we reviewed our prospectively maintained GC database and included individuals diagnosed with clinical stage II-III GC who received neoadjuvant therapy followed by surgery between January 2022 and August 2023. The treatment protocol combined ICIs, anti-angiogenic therapy (specifically apatinib), and chemotherapy (S-1 with oxaliplatin). A systematic approach was used to document patients’ clinical and pathological characteristics, pathological findings, and survival outcomes, which were subsequently analyzed in detail.ResultsA total of 38 individuals met the study’s inclusion criteria, with the majority (32 patients, 84.2%) having clinical stage III GC. All participants underwent surgery, resulting in a notable R0 resection rate of 97.4%. The rates of major pathological response (MPR) and pathological complete response (pCR) were 47.4% and 23.7%, respectively. Post-surgery, 36 patients (92.1%) received adjuvant chemotherapy. With a median follow-up of 22 months, ten patients experienced disease recurrence, including three who died from tumor relapse. The 1-year overall survival (OS) rate stood at 100%, and the disease-free survival (DFS) rate was 94.7%, with median OS and DFS yet to be reached. The neoadjuvant therapy regimen was generally well-tolerated, with no grade 5 treatment-related adverse events (TRAEs) reported. Only one patient experienced a grade 4 TRAE (immune-related hepatitis), while the most common grade 3 TRAEs included thrombocytopenia, elevated aminotransferase levels, and neutropenia.ConclusionsThe combination of neoadjuvant chemotherapy, anti-angiogenic therapy, and ICIs has proven effective in treating LAGC patients, achieving high pCR rates and favorable survival outcomes while maintaining an acceptable safety profile.